The link between external and internal shame and binge eating: The mediating role of body image-related shame and cognitive fusion - Melo, Daniela Catarina Cardoso (2019)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação